The Spatio-temporal Characteristics of Land Surface Temperatures in Shanghai, and Their Responses to Land-use Change - Jiang, Rong; Zhang, Yan; Chen, Liang; Xiang, Weining; Liu, Gengyuan; Zheng, Hongmei (Journal of Environmental Accounting and Management, 2026)
The continuous expansion of impervious artificial surfaces in cities has significantly influenced the urban thermal environment. Recent advances in remote-sensing techniques and geographic information systems have made it possible to investigate the thermal characteristics of the urban environment at a city scale. In the present study, we performed spatial, temporal, and consistency analysis of land surface temperatures (LST) and land use by using Landsat TM thermal infrared remote-sensing images to derive the spatial patterns of urban LST and its changes in Shanghai from 1987 to 2000, meanwhile we also analyzed the relationship between the LST distribution and land-use patterns. We found that the LST distribution was closely related to the land-use pattern: construction land tended to have high LST, whereas vegetation and water body mainly had low LST. We further classified Shanghai's urban thermal environment into five temperature classes; changes inthese classes defined three temperature trends. Using 2000 as an example, we analyzed the consistency of the relationship between LST and land use to examine the impact of urban land use on the urban thermal environment. The results showed that our approach was a feasible way to examine urban LST and its evolution, and revealed a strong relationship between land use and LST. For the future research, it is also reasonable to focus on longer time series and more land-use types.